ESTUDO DAS PROPRIEDADES ESTRUTURAIS, MECÂNICAS E ELETRÔNICAS DE NANOTUBOS DE CARBONO DE UMA, DUAS E TRÊS CAMADAS SOB DEFORMAÇÃO ESTRUTURAL - Carmo, Paulo Inácio Obregon do (2018)
Carbon Nanotubes (CNTs) they are object of intense theoretical and experimental researches, tends in view the extreme sensibility of their electronic properties, deformations and to defects in the hexagonal net to alterations in the structural parameters. The structural and electronic properties of CNTs have been considered the base for the development of coverings nanoestruturados destined to the research space, sensor and fotovoltaics devices, among others. A better knowledge of the properties of these materials is necessary so that we can project more efficient and durable devices, besides assisting to crescent it disputes of the market of technological innovation. In this work analyses of the elastic and electronic properties of single-walled nanotubes carbon (SWCNT) and multi-walled with two (DWCNT) and three (TWCNT) shells deformed by axial traction were accomplished. The structural and energy properties of CNTs studied were obtained through calculations of first beginnings, with base in the Theory of the Functional of the Density, that one find implemented in the program SIESTA (Spanish Initiative goes Electronic Simulations with Thousand of Atoms). Considering CNTs discreet shells and making use of the mechanics solids continuous, we obtained that the elasticity modulus varies of 0,65TPa - for the nanotubo (4,4), to 0,95 TPa - for NTC (10,10). It was verified that the mechanical resistance increases with the diameter of CNT, except for CNT (15,15) that presents smaller mechanical resistance than CNT (10,10). We determined with base in the variation of the elastic energy and of the connection length the modulus of young. We observed that the nanotubos with different layers have behaviors differentiated front to the tensions, so much in points of rupture of the chemical structure, when to the electronic properties. Nanotubes of carbon of the type armchair are metallic, however starting from certain deformations, they become semiconductors and their energy gap varies in agreement with the intensity of the applied tension.